Health and home ownership: Findings for the case of Japan - Toshiaki Aizawa; Matthias Helble (Asian Development Bank Institute (ADBI), 2015)
The research objective of this paper is to test whether health conditions and health behavior are related to home ownership. This question has not yet been examined quantitatively in the existing literature. Our estimation results show that homeowners consistently report better health and less physical problems. The significance of home ownership remains even after controlling for financial assets and housing conditions. Furthermore, our estimations indicate that homeowners invest more in their future health by undergoing voluntarily medical screenings more frequently. Finally, our estimations suggest that home ownership is positively correlated with health care expenditure even when controlling for income, debt, and other financial assets and we could not reject the exogeneity of home ownership. Our empirical results thus provide evidence for the importance of home ownership for health.
Keywords: I12; I15; 330; health; home ownership; housing conditions; grossman model; medical expenditures